Prevalence of leptospira-agglutinating antibodies in abattoir workers and slaughtered animals in selected slaughterhouses in Cavite, Philippines - Tabo, Norbel A.; Villanueva, Sharon Yvette Angelina M.; Gloriani, Nina G. (2018)
Leptospirosis is known to be endemic in the Philippines with high incidence during rainy season or after heavy rains in flood-prone areas. The aim of this study was to determine the prevalence of antibodies against Leptospira in abattoir workers and slaughtered animals in selected slaughterhouses in Cavite, Philippines. Serum samples obtained from 46 abattoir workers and 69 slaughtered animals were subjected to microscopic agglutination test. Results showed that 15.2% of abattoir workers in the study sites were positive for Leptospira-agglutinating antibodies against L. interrogans serovar (sv) Canicola, Losbanos, and Ratnapura; L. fainei sv Hurtsbridge; and L. borgpetersenii sv Poi. On the other hand, the overall Leptospira-seropositivity in slaughtered animals was 58.0%, 61.7% of which was in pigs and 33.3% in cows. The most frequently occurring serovar in pigs was Poi with 38.3%, followed by L. interrogans sv Icterohaemorrhagiae strain Ictero No. 1 (18.3%), Copenhageni (16.7%), and Icterohaemorrhagiae strain RGA (8.3%). On the other hand, the most frequently occurring serovar in cows was Poi (22.2%). The presence of common serovars in abattoir worker-slaughtered animal interface could indicate continual source of leptospires and could pose problems on human health. These serovars could be potential candidates for the development of vaccines and diagnostic tests.